Clay Filled Aluminum Product - Mohd Ichwan, Nasution, Ir. (Malaysian Invention and Design Society (MINDS), 2010)
Ir. Mohd Ichwan Nasution and his team won gold for Clay Filled Aluminum Product. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.